DESIGN ANALYSIS OF THE STRENGTH OF STRAIGHT (VERTICAL) PIPE CONNECTIONS USING MODIFIED FLANGES IN DEEP WELL PUMP PIPE INSTALLATIONS - LUMBANTORUAN, CRISTOVEL; ST, M.T., Nurato (Universitas Mercu Buana, 2025)
Strength Analysis of Straight (Vertical) Pipe Connections Using Modified Flange on Deep Well Pump Pipe Installation is an important part of the oil and natural gas industry, because it functions to drain fluid from the well to the oil gathering station. Well pump pipelines must be well designed to ensure safety and operational efficiency. One of the important components in the well pump pipeline design is the straight (vertical) pipe connection using a modified flange. The strength analysis of this straight pipe connection is carried out to determine how the modified flange affects the strength of the pipe connection. The method used is a design analysis of the strength of straight pipe joints using modified flanges with reference to international codes and simulations using Solidworks software. The results show that the flange must be modified because it is for the cable line and adjusts to the diameter of the well which is 8' in diameter. The strength of straight pipe joints is also affected by pipe diameter, operating pressure, and pipe material type. The conclusion of this analysis is that the modified flange can reduce the strength of the straight pipe connection, so it requires proper consideration and calculation. Therefore, the modified flange should be considered in the well pump pipeline design to ensure safety and operational efficiency